The Effectiveness of a Health Provider Led Education Intervention on Improving Patient Rights Awareness among Pregnant Women attending Antenatal Care Clinics in Kenya - Chepkorir, Egla; Nyaberi, Jackline; Mutai, Joseph (Global Journal of Health Sciences, 2025)
Purpose: According to WHO, a third of women experience mistreatment during childbirth and this affect their health outcomes. Patient rights are essential for promoting quality healthcare. However, awareness of these rights, particularly vulnerable groups such as pregnant women, remains low in many healthcare settings especially the rural and peri-urban settings, where 98% of maternal morbidity and mortality could be prevented by timely and appropriate healthcare. This study aimed to determine the effectiveness of a health provider led education intervention on improving knowledge on patient rights awareness among pregnant women attending antenatal clinics in Kenya. Methodology: A quasi-experimental design where convergent parallel design was adopted. A Pre and post intervention studies were conducted in selected antenatal clinics in Kenya. A total of 168 pregnant women participated, with 96 in the intervention group and 72 in the control group. The intervention was delivered by healthcare providers through educational forums held within the health facility. Data were collected using an interviewer administered questionnaire, and statistical analysis was performed using SPSS v25 to evaluate the changes in awareness levels. Findings: The results showed a significant improvement in awareness of patient rights among the intervention group, with knowledge of the patients' rights charter increasing from 19.8% pre-intervention to 67.8% post-intervention (p < 0.001). The proportion of pregnant women who acknowledged receiving information regarding patient rights increased from 3.1% to 71.1% (p < 0.001). Majority of the respondents cited healthcare providers (68.4%), health facilities (31.6%), media (47.4%), and others (15.8%) as the sources of information. Additionally, the quality of services rated by mothers improved significantly from 35.5% to 53% at end line, with a decline of those who reported being dissatisfied with the services received from 17% to 13.3%. Unique Contribution to Theory, Practice and Policy: Raising awareness and ensuring respect for patients' rights are essential for improving the quality of maternal care. These findings highlight the significance of educating women about their healthcare rights, as increased awareness is directly liked to utilization of maternal health services and better health outcomes. Educational sessions delivered by healthcare providers offer significant benefits, emphasizing the importance of continuing these valuable sessions and other services provided at healthcare facilities. These findings also highlight the need for policy makers to incorporate continuous training and the development of educational content for healthcare providers to ensure long-term sustainability.